SIMPLE RULES FOR CONDUCTING ATHLETICS COMPETITIONS IN SCHOOLS (Scientific journal of the Fergana State University, 2023)
This article describes the conduct of the competition in accordance with the regulations drawn up and approved by the relevant organization. The regulation is the main document of the competition that regulates the competition. A jury is appointed to conduct them.